Pengetahuan dan Sikap Ibu Nifas tentang Perawatan Luka Perineum - Rini Hariani Ratih (Jurnal Kesmas Asclepius, 2020)
This study aimed to determine the relationship between the mother's knowledge and attitudes about care for perineal wounds. This research uses quantitative research. The research design used was cross-sectional. The results of the study are based on analysis using the chi square> 0.05 statistical test. It is known that the p-value is 0.02 for the knowledge variable and 0.04 for the attitude variable. In conclusion, there is a significant relationship between knowledge and wound care perineum; there is a relationship between postpartum attitudes to care for perineal wounds. Keywords: Postpartum, Knowledge, Perineal Wound Care, Attitude